Preparation method of composite aerogel

By combining Bacillus subtilis extracellular polysaccharide EPS with carbon nanotube CNT, and forming a stable EPPS/CNT composite aerogel through acetylation and crosslinking reaction, the problems of poor thermal insulation performance and environmental impact of existing grain storage materials are solved, and efficient and stable grain storage effect is achieved.

CN119633703APending Publication Date: 2025-03-18SHANGQIU PROD QUALITY INSPECTION & TESTING RES CENT +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411928140.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The existing grain storage materials have poor thermal insulation performance, non-renewable, and low storage efficiency, which can easily cause food loss. The preparation process has high energy consumption, is harmful to the environment, and is unstable in product performance.

Method used

Using the preparation method of composite aerogel, a stable EPPS/CNT composite aerogel is formed by combining Bacillus subtilis extracellular polysaccharide EPS with carbon nanotube CNT and acetylation and cross-linking reaction.

Benefits of technology

It improves the structural and performance stability of composite aerogels, enhances its thermal insulation and mechanical properties, reduces grain storage costs, and reduces energy consumption and harmful substance emissions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119633703A_ABST
    Figure CN119633703A_ABST
Patent Text Reader

Abstract

According to the preparation method of the composite aerogel disclosed by the invention, the composite aerogel has good environmental adaptability due to the selected raw materials and the formed stable structure in the preparation process. The grain storage device can normally work in grain storage environments with different temperatures, humidity and the like, and the performance of the grain storage device is not easily reduced due to the influence of environmental factors. For example, in a high-temperature and high-humidity environment, due to the porous structure and the stable chemical structure of the aerogel, the aerogel still can effectively insulate heat and keep the structure complete, the grain deterioration risk caused by environmental factors is reduced, the grain storage safety is improved, and energy consumption and emission of harmful substances are reduced; meanwhile, the performance stability and the environmental adaptability of the composite aerogel are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of grain storage, and in particular to a method for preparing a composite aerogel. Background Art

[0002] In the process of grain storage, it is necessary to place insulating materials in the grain pile to achieve the purpose of insulation. The principle of insulating materials in grain storage is: Slow down heat transfer: The thermal conductivity of the insulation material is low, and it can form a thermal resistance layer between the grain pile and the outside world. When the outside temperature changes, it can prevent heat from entering and leaving the grain pile quickly, such as preventing heat from entering in summer and slowing down heat loss in winter, so as to maintain a stable temperature inside the grain pile.

[0003] Stabilize the physical and chemical properties of grain: Grain has a respiration function and is affected by temperature. Insulation materials keep the temperature of the grain pile constant to prevent temperature fluctuations from affecting grain respiration and metabolism. Too high a temperature will accelerate respiration, leading to nutrient consumption and increased moisture, which can easily cause mildew and insect pests; too low a temperature may cause frostbite on the grain. Stable temperature can extend the storage life of grain.

[0004] Prevent moisture problems: Temperature changes can cause moisture migration in the grain pile. Large temperature differences may cause condensation, which increases the moisture content of local grains and is conducive to the breeding of microorganisms and pests. Insulation materials reduce moisture migration and condensation caused by temperature differences, keep moisture evenly distributed in the grain pile, and reduce the risk of moisture, mold, and pests.

[0005] Existing grain storage commonly uses: Polyurethane foam board: excellent thermal insulation performance, low thermal conductivity, closed-cell structure to prevent gas convection. Lightweight, easy to install and cut, commonly used for thermal insulation of grain warehouse walls and roofs.

[0006] Polystyrene foam board (EPS): It has good thermal insulation performance and physical stability, mature production technology, low cost, wide application, and certain moisture-proof performance, which can protect food quality.

[0007] Expanded perlite and its products: natural inorganic thermal insulation materials, light weight, heat insulation, fireproof, sound absorption. Made by high temperature roasting and expansion of perlite ore, the microporous structure prevents heat conduction, and the products can be used for laying at the bottom of grain piles or wrapping around them.

[0008] Aerogel felt: a new type of thermal insulation material with extremely low thermal conductivity, high porosity, low density, good thermal insulation effect, and can achieve efficient thermal insulation in thin thickness, but the cost is relatively high. It is increasingly used in grain storage facilities with high insulation requirements or limited space.

[0009] Traditional grain storage materials have poor insulation performance, non-renewable, low storage efficiency, and easy to cause grain loss. In addition, there are also problems such as environmental pollution, chemical residues, and high costs. The preparation process has high energy consumption, is harmful to the environment, and the product performance is unstable. In addition, due to its extremely high porosity (up to 99.8%), extremely low density (as low as 3 kilograms per cubic meter), extremely high specific surface area (up to 2,000 square meters per gram), ultra-high pore volume rate, high temperature resistance, high elasticity, strong adsorption, catalysis and other characteristics. In addition, aerogel has a very low thermal conductivity and is currently used for grain storage. The thermal insulation and heat preservation performance of the material is good.

[0010] EPS / CNT composite aerogel combines the biocompatibility of EPS and the mechanical properties of CNT, making it an optimal material for grain storage. However, maintaining its structural stability during the preparation process is a major challenge. Summary of the invention

[0011] The purpose of the present invention is to provide a method for preparing a composite aerogel, thereby improving the stability of the composite aerogel structure and performance, thereby improving the efficiency and safety of grain storage, and also greatly reducing the grain storage cost.

[0012] The object of the present invention is achieved in that: A method for preparing a composite aerogel comprises the following steps: Step S1, weighing a set amount of Bacillus subtilis extracellular polysaccharide EPS, and dissolving the Bacillus subtilis extracellular polysaccharide EPS in a set amount of distilled water to obtain an EPS solution; Step S2, weighing sodium carbonate powder using an electronic balance, and slowly adding the sodium carbonate powder to the EPS solution of step S1 to obtain a mixed solution; the sodium carbonate powder is added to acetylate the Bacillus subtilis extracellular polysaccharide EPS, change the chemical structure and properties of the Bacillus subtilis extracellular polysaccharide EPS, and enhance the crosslinking between the Bacillus subtilis extracellular polysaccharide EPS and the crosslinker BDDE to participate in subsequent reactions.

[0013] Step S3: Use a pipette to measure a set amount of the crosslinking agent 1,4-butanediol diglycidyl ether, and drip the crosslinking agent 1,4-butanediol diglycidyl ether into the mixed solution of step S2 to obtain a reaction solution; during the dripping process, pay attention to maintaining a stable dripping speed and a uniform dripping method to avoid excessive local concentration or too fast reaction, so that the crosslinking agent can fully contact with EPS and undergo a crosslinking reaction. The crosslinking reaction is crucial to the formation of a stable gel structure. It can form chemical bonds between molecules and enhance the stability and integrity of the material. Step S4, using a balance to weigh a set amount of carbon nanotubes CNT, and uniformly dispersing the carbon nanotubes CNT in the reaction solution of step S3 by ultrasonic dispersion treatment to obtain a gel solution; such uniform dispersion can ensure that the carbon nanotubes are evenly distributed in the entire system and avoid the occurrence of agglomeration, thereby giving full play to the reinforcing effect of the carbon nanotubes in the composite aerogel; Step S5, transferring the gel solution of step S4 to a refrigerator for pre-freezing treatment to obtain pre-frozen gel; the pre-freezing process can cause the water in the gel solution to form ice crystals, and the formation mode and size of the ice crystals will affect the pore structure of the aerogel after subsequent freeze drying. Step S6, placing the pre-frozen gel of step S5 in a freeze dryer for freeze drying treatment, during the freeze drying process, the ice crystals directly sublimate, thereby forming a porous structure inside the material, and finally obtaining EPPS / CNT composite aerogel.

[0014] In the step S1, during the dissolution process, a magnetic stirrer is used to continuously stir at 800 rpm for two hours to fully dissolve the Bacillus subtilis extracellular polysaccharide EPS in the distilled water to form a uniform EPS solution.

[0015] In the step S1, 0.07 g of Bacillus subtilis extracellular polysaccharide EPS and 5 ml of distilled water were weighed.

[0016] In step S2, the amount of sodium carbonate powder used is 0.005-0.015 g.

[0017] In the step S3, the amount of the cross-linking agent 1,4-butanediol diglycidyl ether is 80 to 100 ml.

[0018] In the step S4, the carbon nanotubes CNT are 0.04-0.08 g.

[0019] In step S5, the temperature in the refrigerator is -80°C and the pre-freezing time is 10 hours.

[0020] In step S6, the freeze dryer is used for two days at a freezing temperature of -80°C.

[0021] The beneficial effects of the present invention are: Improved performance stability: Through precise operation of raw material processing, reaction control, structure construction and processing in each step, the performance stability of composite aerogel is fully guaranteed from the molecular level to the macro structure. Whether it is the modification of chemical structure, the control of cross-linking reaction, or the regulation of microstructure (such as pore structure) and macrostructure (such as shape stability), composite aerogel can maintain its performance under different environmental conditions, such as thermal insulation performance, mechanical properties, etc., with small fluctuations, so that it can be reliably used in food storage.

[0022] Enhanced environmental adaptability: The raw materials selected during the preparation process (such as biocompatible EPS and excellent carbon nanotubes) and the stable structure formed make the composite aerogel have good environmental adaptability. It can work normally in grain storage environments with different temperatures and humidity, and is not easily affected by environmental factors and its performance degraded. For example, in a high temperature and high humidity environment, the porous structure and stable chemical structure of the aerogel enable it to effectively insulate and maintain structural integrity, reduce the risk of grain deterioration caused by environmental factors, and improve the safety of grain storage.

[0023] Reduced energy consumption and emissions: The entire preparation process may reduce energy consumption and harmful emissions compared to traditional methods. For example, the selection and treatment of raw materials may reduce energy consumption during the synthesis process, while the reagents and processes used are relatively environmentally friendly and reduce the generation of harmful waste. This meets the requirements of sustainable development and also reduces production costs. It has both economic and environmental benefits in the field of grain storage, and helps promote the development of green grain storage technology.

[0024] The invention reduces energy consumption and emission of harmful substances, and simultaneously improves the performance stability and environmental adaptability of the composite aerogel. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 It is a schematic diagram of the structure of the present invention. DETAILED DESCRIPTION

[0026] The present invention is further described below in conjunction with the accompanying drawings and embodiments.

[0027] like Figure 1 As shown, a method for preparing a composite aerogel comprises the following steps: Step S1, weighing 0.05 g of Bacillus subtilis extracellular polysaccharide EPS-, extracting the polysaccharide synthesized by Bacillus subtilis, and dissolving the Bacillus subtilis extracellular polysaccharide EPS in 4 ml of distilled water to obtain an EPS solution.

[0028] During the dissolution process, a magnetic stirrer was used to continuously stir at 800 rpm for two hours to fully dissolve the Bacillus subtilis exopolysaccharide EPS in distilled water to form a uniform EPS solution.

[0029] Step S2, using an electronic balance to weigh 0.005 g of sodium carbonate powder, and slowly adding the sodium carbonate powder to the EPS solution of step S1 to obtain a mixed solution; the sodium carbonate powder is added to acetylate the Bacillus subtilis extracellular polysaccharide EPS, change the chemical structure and properties of the Bacillus subtilis extracellular polysaccharide EPS, and enhance the crosslinking between the Bacillus subtilis extracellular polysaccharide EPS and the crosslinker BDDE to participate in subsequent reactions.

[0030] Step S3, using a pipette to measure 80 ml of the cross-linking agent 1,4-butanediol diglycidyl ether, and dripping the cross-linking agent 1,4-butanediol diglycidyl ether into the mixed solution of step S2 to obtain a reaction solution; during the dripping process, attention should be paid to maintaining a stable dripping speed and a uniform dripping method to avoid excessive local concentration or too fast reaction, so that the cross-linking agent can fully contact with EPS and undergo a cross-linking reaction. The cross-linking reaction is crucial to forming a stable gel structure, which can form chemical bonds between molecules and enhance the stability and integrity of the material.

[0031] Step S4, using a balance to weigh 0.005 g of carbon nanotubes CNT, and uniformly dispersing the carbon nanotubes CNT in the reaction solution of step S3 by ultrasonic dispersion treatment to obtain a gel solution; this uniform dispersion can ensure that the carbon nanotubes are evenly distributed in the entire system, avoid the occurrence of agglomeration, and thus give full play to the reinforcing effect of the carbon nanotubes in the composite aerogel.

[0032] Step S5, transferring the gel solution of step S4 to a refrigerator for pre-freezing to obtain pre-frozen gel; the pre-freezing process can cause the water in the gel solution to form ice crystals, and the formation mode and size of the ice crystals will affect the pore structure of the aerogel after subsequent freeze drying. The temperature in the refrigerator is -80°C, and the pre-freezing time is 10 hours.

[0033] Step S6, placing the pre-frozen gel of step S5 in a freeze dryer for freeze drying. During the freeze drying process, ice crystals directly sublimate, thereby forming a porous structure inside the material, and finally obtaining EPPS / CNT composite aerogel. Freeze at -80°C in the freeze dryer for two days. Bacillus subtilis exopolysaccharide EPS is extracted by the applicant from polysaccharides synthesized by Bacillus subtilis.

[0034] Sodium carbonate was purchased from Shanghai Maclean Biochemical Technology Co., Ltd.; the cross-linking agent 1,4-butanediol diglycidyl ether was purchased from Shanghai Maclean Biochemical Technology Co., Ltd.; carbon nanotubes CNT were purchased from Shanghai Maclean Biochemical Technology Co., Ltd.; chloroform was purchased from Tianjin Kaitong Chemical Reagent Co., Ltd.; n-butanol was purchased from Tianjin Kaitong Chemical Reagent Co., Ltd.; and ethanol was purchased from Tianjin Zhiyuan Chemical Reagent Co., Ltd.

[0035] Among them, chloroform and n-butanol are used to prepare Sevage reagent, which is used to remove proteins from the fermentation broth during the EPS extraction process. The specific operation is to use a vortex mixer to fully shake and mix the fermentation broth and Sevage reagent, centrifuge at 4°C and 8000rpm for 30 minutes, and extract repeatedly until there is no white precipitate between the sample and the Sevage reagent. Ethanol is used to precipitate polysaccharides during the EPS extraction process. Three times the volume of anhydrous ethanol is added to the supernatant after protein removal, and the precipitate is obtained by centrifugation. The energy-saving core ultra-low temperature preservation box is Zhongke Meiling DW-HL680; the prepared composite aerogel sample is placed in the energy-saving core ultra-low temperature preservation box to prevent it from deteriorating or changing in performance before subsequent performance tests. The freeze dryer is SPScientificLyoStar4.0; the refrigerator is Midea BCD-220VM.

[0036] Experimental results: This experiment conducted multiple groups of experiments with EPS ranging from 0.05g to 0.1g. The results are now explained using the example of an EPS dosage of 0.07g when the optimal composite aerogel yield is 1.1g.

[0037] Raw material preparation Accurately weigh 0.07g of Bacillus subtilis extracellular polysaccharide EPS, prepare 5ml of distilled water, and appropriate amounts of sodium carbonate powder (0.005 - 0.015g), crosslinking agent 1,4-butanediol diglycidyl ether (80 - 100ml), and carbon nanotubes CNT (0.04 - 0.08g). At the same time, ensure that the magnetic stirrer, electronic balance, pipette, balance, refrigerator, freeze dryer and other instruments are operating normally.

[0038] Solution preparation (step S1) 0.07 g of EPS was placed in a container, 5 ml of distilled water was added, and the magnetic stirrer was turned on and stirred at 800 rpm for two hours until the EPS was completely dissolved to form a uniform EPS solution.

[0039] Acetylation treatment (step S2) Use an electronic balance to weigh 0.01g (take the middle value as an example) of sodium carbonate powder, and slowly add it to the EPS solution to make the EPS undergo acetylation reaction, change its chemical structure and properties, and enhance its cross-linking ability with the cross-linking agent.

[0040] Cross-linking reaction (step S3) Use a measuring cylinder to measure 90 ml (take the middle value as an example) of the cross-linking agent 1,4-butanediol diglycidyl ether, and use a pipette to slowly and evenly drop it into the above mixture to ensure that the cross-linking agent and EPS are fully in contact and cross-linking reaction occurs, so that the solution gradually forms a gel state.

[0041] Carbon nanotube dispersion (step S4) Weigh 0.06g (take the middle value as an example) of carbon nanotubes CNT on a balance and add it to the reaction solution. Use ultrasonic dispersion treatment to make the carbon nanotubes evenly dispersed in the system to play a reinforcing role.

[0042] Pre-freezing process (step S5) The gel solution was transferred to a -80°C refrigerator and pre-frozen for 10 hours to allow the water to form ice crystals. The ice crystal structure affected the subsequent aerogel pore structure.

[0043] Freeze drying (step S6) After the pre-freezing was completed, the pre-frozen gel was placed in a -80°C freeze dryer and dried for two days. The ice crystals sublimated to form a porous structure, and finally EPPS / CNT composite aerogel was obtained with a yield of 1.1 g.

[0044] Process control and optimization After multiple experimental comparisons, it was determined that under the above conditions, the optimal yield of 1.1g composite aerogel can be obtained using 0.07g EPS as raw material, providing a basis and optimization direction for large-scale preparation and application.

Claims

1. A method for preparing a composite aerogel, characterized in that: The following steps are involved: Step S1, weighing a set amount of Bacillus subtilis extracellular polysaccharide EPS, and dissolving the Bacillus subtilis extracellular polysaccharide EPS in a set amount of distilled water to obtain an EPS solution; Step S2, using an electronic balance to weigh a set amount of sodium carbonate powder, and adding the sodium carbonate powder to the EPS solution of step S1 to obtain a mixed solution; the sodium carbonate powder is added to acetylate the Bacillus subtilis exopolysaccharide EPS; Step S3, using a pipette to measure a set amount of a cross-linking agent 1,4-butanediol diglycidyl ether, and dripping the cross-linking agent 1,4-butanediol diglycidyl ether into the mixed solution of step S2 to obtain a reaction solution; Step S4, using a balance to weigh a set amount of carbon nanotubes CNT, and using an ultrasonic dispersion treatment method to evenly disperse the carbon nanotubes CNT in the reaction solution of step S3 to obtain a gel solution; Step S5, transferring the gel solution of step S4 to a refrigerator for pre-freezing to obtain a pre-frozen gel; Step S6, placing the pre-frozen gel in step S5 in a freeze dryer for freeze drying. During the freeze drying process, ice crystals sublimate directly, thereby forming a porous structure inside the material, and finally obtaining EPPS / CNT composite aerogel.

2. The method for preparing the composite aerogel according to claim 1, characterized in that: In the step S1, during the dissolution process, a magnetic stirrer is used to continuously stir at 800 rpm for two hours to fully dissolve the Bacillus subtilis extracellular polysaccharide EPS in the distilled water to form a uniform EPS solution.

3. The method for preparing the composite aerogel according to claim 1, characterized in that: In the step S1, the amount of Bacillus subtilis extracellular polysaccharide EPS weighed is 0.05g-0.1g, and the amount of distilled water used ranges from 4ml to 6ml.

4. The method for preparing the composite aerogel according to claim 1, characterized in that: In step S2, the amount of sodium carbonate powder used is 0.005-0.015 g.

5. The method for preparing the composite aerogel according to claim 1, characterized in that: In the step S3, the cross-linking agent 1,4-butanediol diglycidyl ether is 80-100 ml.

6. The method for preparing the composite aerogel according to claim 1, characterized in that: In the step S4, the mass of the carbon nanotubes CNT is 0.04-0.08 g.

7. The method for preparing the composite aerogel according to claim 1, characterized in that: In step S5, the temperature in the refrigerator is -80°C and the pre-freezing time is 10 hours.

8. The method for preparing the composite aerogel according to claim 1, characterized in that: In step S6, the freeze dryer is kept for two days at a freezing temperature of -80°C.